Bibliometric Analysis of Factors Affecting Performance and Completeness of Electronic Medical Records (EMR) in Primary Health Services - Gendis Ratri Kusuma Wardhani; Rosihan Adhani; Abdullah Oski Illiandri; Musafaah Musafaah; Iwan Alfarie (Malahayati Nursing Journal, 2024)
ABSTRACT Electronic Medical Records (EMR) completeness and accuracy are fundamental to effective patient care, clinical decision-making, and overall healthcare management. In recent years, there has been increasing attention to improving EMR documentation by healthcare professionals to improve data quality and patient care outcomes. This bibliometric study aimed to explore the trends, research focus, and gaps in the literature regarding EMR completeness from 2019 to 2024. The study used Publish or Perish software to collect data from Google Scholar with specific keywords such as Performance, Factors, Electronic Medical Record (EMR), EMR Completeness, Primary Healthcare, Filling, Documentation, and Medical Record Accuracy. The analysis included the 30 highest ranked journals. In addition, VOS Viewer was used for network visualization, overlay, and density to analyze thematic linkages and identify potential research gaps. Bibliometric analysis showed that Indonesia, the United States, and Ethiopia were the main contributors in EMR-related publications. Frequent themes such as data completeness, quality, and accuracy, emphasize their crucial role in the EMR research field. These findings emphasize the importance of continuously improving EMR data completeness and accuracy, which are critical for reliable clinical decision making and effective healthcare delivery. Future research should focus on developing methodologies to improve data quality and integration of EMR systems with other health information systems. In addition, exploration of policy and regulatory implications related to EMR completeness may provide valuable insights for healthcare practice. Keywords: EMR Completeness, Data Quality, Bibliometric Analysis, Health Documentation, VOS Viewer.